Abstract 1122‐000208: Imaging Characteristics for Post Stroke Delirium - Mohammad Jamil Ahmad; Sahar Anjum; Aditya Kumar; Jacob Sebaugh; Michele Joseph; Bethany Williams; Alicia Zha (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Delirium after acute ischemic stroke (AIS) is a common clinical occurrence, present in 13–48% of patients. Post‐stroke delirium is associated with longer hospital admissions, worse functional outcomes, and increased mortality in the short term and has been associated with worse long‐term outcomes. Prior studies have shown right‐sided strokes are more associated with delirium, but very few other imaging characteristics of post‐stroke delirium have been described. We conducted a prospective study evaluating imaging characteristics for patients with delirium. Methods: Between Sept 2019 and June 2021, patients diagnosed with AIS within 48 hrs of stroke onset were prospectively evaluated for delirium using the Confusion Assessment Method (CAM)‐ICU daily for the first eight days of their hospital stay. Patients with severe stroke and expected mortality within the first month at the time of admission or with severe aphasia unable to follow commands were excluded. Data regarding demographics, comorbidities, hospital stay, stroke metrics, lab work and medications were analyzed. Imaging characteristics were adjudicated by authors based on either the patient’s first MRI or the 24 hr CT after admission. Infarct size measured based on ABC/2 formula based on diffusion‐weighted imaging on MRI or stroke appearance on CT. Results: Over the course of 12 non‐consecutive months, we evaluated 213 patients, of which 177 could be assessed with the CAM‐ICU. Delirium was present in 88 (49.7%). There were no statistically significant differences in age, gender, race, co‐morbidities, or TOAST etiology among patients with and without delirium (Table 1). Patients with delirium had higher NIHSS and were more likely to receive tPA. Patients with delirium were more likely to have MCA territory strokes, strokes involving the insula, and to have infarct sizes ≥10 cc. On multivariate modeling, NIHSS (OR 1.07; 95% CI 1.01, 1.13), MCA territory stroke (OR 2.62; 95% CI 1.09, 6.30), and infarct size ≥10 cc (OR 3.23; 95% CI 1.46, 6.90) were associated with delirium. Conclusions: In a cohort of AIS patients without significant expected mortality on admission, the incidence of delirium is high. On evaluation, infarct size ≥10 cc and in the MCA territory were more associated with delirium than NIHSS. These imaging characteristics should be considered in any future predictive models for identifying patients at risk for delirium.